Positive electrode active material for lithium ion secondary battery and lithium ion secondary battery
By employing lithium transition metal-containing composite oxide particles with a metal complex oxide coating, the positive electrode active material addresses limitations in output characteristics, achieving improved lithium ion conductivity and reduced internal resistance for enhanced battery performance.
Patent Information
- Application Number
- JP2021547000
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-19
- Filing Date
- 2020-09-18
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-09-18
AI Technical Summary
Existing positive electrode active materials for lithium-ion secondary batteries have limitations in achieving optimal output characteristics, particularly in reducing internal resistance and enhancing thermal stability.
The development of a positive electrode active material composed of lithium transition metal-containing composite oxide particles with a layered rock salt type crystal structure, coated with a metal complex oxide layer containing elements like Al, Ti, Zr, Nb, Mo, and W, which enhances lithium ion conductivity and reduces reaction resistance.
This solution significantly improves the output characteristics of lithium-ion secondary batteries by increasing the contact area with the electrolyte, promoting efficient lithium ion insertion and desorption, and reducing internal resistance, thereby enhancing battery durability and performance.
Smart Images

Figure 0007660064000003 
Figure 0007660064000004 
Figure 0007660064000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for lithium ion secondary batteries, which is made of a lithium transition metal-containing composite oxide, and to a lithium ion secondary battery using the positive electrode active material for lithium ion secondary batteries as a positive electrode material. [Background technology]
[0002] In recent years, with the widespread use of portable electronic devices such as smartphones, tablet terminals, digital cameras, and notebook computers, there is a strong demand for the development of small, lightweight secondary batteries with high energy density. There is also a strong demand for the development of high-capacity, high-output secondary batteries as power sources for electric vehicles such as hybrid electric vehicles, plug-in hybrid electric vehicles, and battery-powered electric vehicles.
[0003] A lithium ion secondary battery is a secondary battery that satisfies such requirements. This lithium ion secondary battery is composed of a negative electrode, a positive electrode, a non-aqueous electrolyte or a solid electrolyte, and the active materials used as the materials for the negative electrode and the positive electrode are materials that can extract and insert lithium. The non-aqueous electrolyte includes a non-aqueous electrolyte solution obtained by dissolving a lithium salt, which is a supporting salt, in an organic solvent, and the solid electrolyte includes an inorganic or organic solid electrolyte that is non-flammable and has lithium ion conductivity.
[0004] Among lithium-ion secondary batteries, those that use lithium transition metal-containing composite oxides with layered rock-salt or spinel crystal structures as the positive electrode material can obtain a voltage of about 4 V, and therefore research, development, and commercialization of these batteries as batteries with high energy density are underway.
[0005] Positive electrode materials for lithium-ion secondary batteries include lithium cobalt composite oxide (LiCoO2), which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2), which uses nickel, which is cheaper than cobalt, and lithium nickel manganese cobalt composite oxide (LiNi 1 / 3 Mn 1 / 3Co 1 / 3 O2), lithium manganese composite oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 A positive electrode active material made of a lithium-transition metal-containing composite oxide such as lithium-sulfur oxide (LiO2) has been proposed.
[0006] In recent years, among these lithium transition metal-containing composite oxides, lithium nickel manganese cobalt composite oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 A ternary positive electrode active material made of lithium nickel manganese cobalt-containing composite oxide (NMC), which contains at least nickel, manganese, and cobalt as transition metals, including CrO2), has attracted attention as a material that has excellent thermal stability, high capacity, good battery capacity cycle characteristics, and can provide high output with low resistance. Lithium nickel manganese cobalt composite oxide is a compound that has a layered rock salt type crystal structure, like lithium cobalt composite oxide and lithium nickel composite oxide.
[0007] Regarding lithium-transition metal-containing composite oxides, the focus of their development is on increasing their output by reducing their internal resistance. In particular, there is a high demand for further reduction in internal resistance to increase output in applications as power sources for electric vehicles.
[0008] In order to improve the output characteristics and cycle characteristics of a positive electrode active material made of a lithium transition metal-containing composite oxide such as a lithium nickel-containing composite oxide or a lithium nickel manganese cobalt-containing composite oxide, it is important to use particles with a small particle size and a narrow particle size distribution. Particles with a small particle size have a large specific surface area, and when used as a positive electrode active material, they can sufficiently secure the reaction area with the electrolyte, and furthermore, the positive electrode can be made thin, and the movement distance of lithium ions between the positive electrode and the negative electrode can be shortened. Therefore, by using particles with a small particle size, it is possible to reduce the positive electrode resistance. In addition, by using particles with a narrow particle size distribution, the voltage applied to the particles in the electrode can be made uniform, making it possible to suppress the decrease in battery capacity due to selective deterioration of the fine particles.
[0009] In order to further improve the output characteristics, research and development is also being conducted on improving the particle structure of lithium transition metal-containing composite oxides. For example, it is considered that forming a space portion into which the electrolyte can enter inside the positive electrode active material is effective for improving the output characteristics. By adopting such a structure, the reaction area with the electrolyte can be increased compared to a positive electrode active material with a solid structure having a similar particle size, so that the positive electrode resistance can be significantly reduced. It is known that the positive electrode active material inherits the particle properties of its precursor, the transition metal-containing composite hydroxide. In other words, in order to obtain a positive electrode active material with a space portion, it is necessary to appropriately control the particle size, particle size distribution, particle structure, etc. of the secondary particles of the transition metal-containing composite hydroxide, which is the precursor.
[0010] For example, JP2012-246199A and WO2012 / 131881A disclose a method for producing transition metal-containing composite hydroxide particles, which serve as a precursor of a positive electrode active material, by a crystallization reaction clearly separated into two stages: a nucleation step in which nucleation is mainly performed, and a particle growth step in which particle growth is mainly performed. In these methods, by appropriately adjusting the pH value and reaction atmosphere in the nucleation step and the particle growth step, transition metal-containing composite hydroxide particles are obtained that have a small particle size and a narrow particle size distribution, and are composed of a low-density center part made of fine primary particles and a high-density outer shell part made of plate-like or needle-like primary particles. The positive electrode active material obtained from such composite hydroxide particles has a hollow structure, which increases the contact area with the electrolyte, making it possible to improve the output characteristics.
[0011] WO2014 / 181891 and JP2018-104276A disclose a method for producing transition metal-containing composite hydroxide particles, which includes a nucleation step in which the pH value of an aqueous nucleation solution containing at least a metal compound containing a transition metal and an ammonium ion donor is controlled to be 12.0 or more and 14.0 or less to generate nuclei, and a particle growth step in which the pH value of an aqueous particle growth solution containing the generated nuclei is controlled to be lower than the pH value of the nucleation step and to be 10.5 or more and 12.0 or less to grow the nuclei, and the initial stage of the nucleation step and the particle growth step are a non-oxidizing atmosphere, and at a predetermined timing in the particle growth step, the atmosphere is switched to an oxidizing atmosphere, and then the atmosphere is switched back to a non-oxidizing atmosphere at least once. This method makes it possible to obtain transition metal-containing composite hydroxide particles which have a small particle size and a narrow particle size distribution, have a core formed by the aggregation of plate-like or needle-like primary particles, and have two layered structures in which a low-density layer formed by the aggregation of fine primary particles and a high-density layer formed by the aggregation of plate-like primary particles are alternately stacked outside the core.
[0012] The positive electrode active material using these transition metal-containing composite hydroxide particles as a precursor has a small particle size, a narrow particle size distribution, and a multi-layer structure having a hollow structure or spaces. Therefore, it is said that the secondary battery using these positive electrode active materials can simultaneously improve the battery capacity, output characteristics, and cycle characteristics. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2012-246199 A [Patent Document 2] WO2012 / 131881 publication [Patent Document 3] WO2014 / 181891 publication [Patent Document 4] JP 2018-104276 A Summary of the Invention [Problem to be solved by the invention]
[0014] However, there is room for improvement in the output characteristics of the positive electrode active materials described in these documents, and further improvement in the output characteristics is therefore required.
[0015] In view of the above problems, an object of the present invention is to provide a positive electrode active material for a lithium ion secondary battery that is capable of exhibiting excellent output characteristics when used in a lithium ion secondary battery. [Means for solving the problem]
[0016] The positive electrode active material for a lithium ion secondary battery according to an embodiment of the present invention is General formula (A): Li 1+u Ni x Mn y Co z M1 tO2 (wherein, -0.05≦u≦0.5, x+y+z+t=1, 0.3≦x≦0.9, 0≦y≦0.5, 0≦z≦0.5, 0≦t≦0.05, and M1 is one or more additive elements selected from Mg, Al, Si, Ca, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W), and a lithium transition metal-containing composite oxide particle having a layered rock salt type crystal structure; and a coating layer present on at least a portion of the surface of the lithium transition metal-containing composite oxide particle and consisting of fine particles and / or a coating of a metal composite oxide of Li and a metal element M2 (M2 is one or more metal elements selected from Al, Ti, Zr, Nb, Mo, and W); Equipped with.
[0017] In particular, the positive electrode active material for a lithium ion secondary battery of the present invention has the following features.
[0018] The lithium transition metal-containing composite oxide particles are composed of secondary particles formed by agglomeration of primary particles.
[0019] The lithium transition metal-containing composite oxide particles having the coating layer have a 50% cumulative diameter d50 and a 2.0m cumulative diameter d20 calculated from a particle size distribution measurement value of 3.0 μm or more and 7.0 μm or less. 2 / g or more 5.0m 2 / g or less BET specific surface area, 1.0 g / cm 3 More than 2.0g / cm 3 and an oil absorption of 30 ml / 100 g or more and 60 ml / 100 g or less.
[0020] For each of a plurality of primary particles among the primary particles, each of which has a primary particle diameter in the range of 0.1 μm or more and 1.0 μm or less, the concentration of the additional element M1 is measured at a plurality of locations by cross-sectional STEM or TEM-EDX analysis, and a coefficient of variation of the concentration of the additional element M1, which is the standard deviation of the concentration of the additional element M1 divided by the average concentration of the additional element M1, is calculated. The coefficient of variation is 1.5 or less.
[0021] The amount of M2 contained in the coating layer is 0.1 atomic % or more and 1.5 atomic % or less based on the total number of atoms of Ni, Mn, and Co contained in the lithium transition metal-containing composite oxide particles. The total amount of M1 and M2 in the entire positive electrode active material for lithium ion secondary batteries is preferably 5 atomic % or less based on the total number of atoms of Ni, Mn, Co, M1, and M2.
[0022] The 50% cumulative diameter d50 of the lithium transition metal containing composite oxide particles having the coating layer is preferably 4.0 μm or more and 6.0 μm or less.
[0023] It is preferable that the index showing the spread of the particle size distribution of the lithium transition metal-containing composite oxide particles having the coating layer, [(d90-d10) / d50] (where d10 is the 10% cumulative diameter obtained from the particle size distribution measurement values, and d90 is the 90% cumulative diameter obtained from the particle size distribution measurement values), is 1.0 or less.
[0024] The lithium transition metal-containing composite oxide particles having the coating layer preferably have a d90 / d10 value of 1.0 or more and 2.0 or less.
[0025] The secondary particles are The secondary particles One or more communication holes that communicate with the outer periphery of the Inside the secondary particle It is preferable that the insulating layer has two or more spaces present therein and communicating with the communicating hole. The number of the communicating holes is preferably two or more. It is preferable that the two or more spaces communicate with the communicating hole or another space.
[0026] The additional element M1 is preferably one or more selected from the group consisting of Mg, Al, Si, Ti, Zr, Nb, Mo, and W. The additional element M1 is preferably Al.
[0027] It is preferable that M2 contained in the coating layer is W, and the metal composite oxide is lithium tungstate.
[0028] The lithium ion secondary battery according to the embodiment of the present invention comprises a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte (non-aqueous electrolyte secondary battery), or comprises a positive electrode, a negative electrode, and a solid electrolyte (solid electrolyte secondary battery), and is characterized in that the positive electrode active material for the lithium ion secondary battery according to the present invention is used as the positive electrode active material used in the positive electrode. Effect of the Invention
[0029] In the positive electrode active material for lithium ion secondary batteries according to the embodiment of the present invention, the contact area with the non-aqueous electrolyte or solid electrolyte is increased, and the lithium transition metal-containing composite oxide particles are coated with a metal composite oxide containing Li, thereby facilitating the insertion and desorption of lithium ions at the interface, thereby improving the output characteristics. Therefore, the lithium ion secondary battery using the positive electrode active material for lithium ion secondary batteries according to the embodiment of the present invention is more durable and can provide high output characteristics, and therefore, its industrial significance is remarkable, particularly in the application as a power source for electric vehicles. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is an SEM photograph of a cross section of a secondary particle constituting the positive electrode active material for a lithium ion secondary battery of Example 1 of the present invention. [Diagram 2] FIG. 2 is an SEM photograph of a cross section of a secondary particle constituting the positive electrode active material for a lithium ion secondary battery of Comparative Example 1. As shown in FIG. [Diagram 3] FIG. 3 is a schematic cross-sectional view of a 2032-type coin battery used in the battery evaluation. [Figure 4] FIG. 4 is a graph showing a measurement example of impedance evaluation. [Diagram 5] FIG. 5 is a schematic explanatory diagram of an equivalent circuit used in the analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] 1. Positive electrode active material for lithium-ion secondary batteries A positive electrode active material for lithium ion secondary batteries according to one embodiment of the present invention (hereinafter referred to as "positive electrode active material") comprises lithium transition metal-containing composite oxide particles (hereinafter referred to as "composite oxide particles") and a coating layer present on at least a part of the surface of the composite oxide particles. In particular, the positive electrode active material for lithium ion secondary batteries according to this embodiment is characterized by satisfying the following requirements (1) to (7).
[0032] (1) Composite oxide particles (1-a) Composition The composite oxide particles are represented by the general formula (A): Li 1+u Ni x Mn y Co z M1 t O2 (wherein, -0.05≦u≦0.5, x+y+z+t=1, 0.3≦x≦0.9, 0≦y≦0.5, 0≦z≦0.5, 0≦t≦0.05, and M1 is one or more added elements selected from Mg, Al, Si, Ca, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W), and has a layered rock-salt type crystal structure.
[0033] In the positive electrode active material of the present invention, the value of u, which indicates the excess amount of lithium (Li), is in the range of -0.05 to 0.5. It is preferably in the range of 0 to 0.50, more preferably in the range of 0 to 0.35. By restricting the value of u to the above range, it is possible to improve the output characteristics and battery capacity of a lithium ion secondary battery using this positive electrode active material as a positive electrode material. On the other hand, if the value of u is less than -0.05, the positive electrode resistance of the secondary battery increases, so that the output characteristics may not be improved. If it exceeds 0.5, not only the initial discharge capacity decreases, but also the positive electrode resistance may increase.
[0034] Nickel (Ni) is an element that contributes to the high potential and high capacity of a secondary battery, and the value of x, which indicates its content, is in the range of 0.3 to 0.9. It is preferably in the range of 0.4 to 0.7, more preferably in the range of 0.4 to 0.6. If the value of x is less than 0.3, the energy density of a secondary battery using this positive electrode active material may not be sufficiently improved. If the value of x exceeds 0.9, the content of other elements that improve output characteristics and durability may decrease, and the characteristics as a positive electrode active material may not be sufficiently obtained.
[0035] Manganese (Mn) is an element that contributes to improving thermal stability, and the value of y, which indicates the content of manganese, is in the range of 0 to 0.5, and preferably in the range of 0.1 to 0.4. If the value of y exceeds 0.5, Mn may be eluted from the positive electrode active material during high-temperature operation, which may deteriorate the charge-discharge cycle characteristics.
[0036] Cobalt (Co) is an element that contributes to improving charge / discharge cycle characteristics and output characteristics, and the value z indicating the content of Co is in the range of 0 to 0.5, preferably 0.1 to 0.4. If the value z exceeds 0.5, the initial discharge capacity of a secondary battery using this positive electrode active material may decrease.
[0037] The positive electrode active material of the present invention may contain the following additive element M1. As the additive element M1, one or more elements selected from magnesium (Mg), aluminum (Al), silicon (Si), calcium (Ca), titanium (Ti), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W) may be used.
[0038] The additional element M1 is preferably at least one selected from the group consisting of Mg, Al, Si, Ti, Zr, Nb, Mo, and W, and is more preferably Al.
[0039] The value of t, which indicates the content of the additive element M1, is in the range of 0 to 0.05. It is preferably in the range of 0.001 to 0.03. If the value of t exceeds 0.05, the amount of metal elements contributing to the Redox reaction decreases, so that the battery capacity of the secondary battery decreases. Note that the metal element M2, which will be described later, is also present in the coating layer, but the total amount of M1 and M2 in the entire positive electrode active material is preferably 5 atomic % or less with respect to the total number of atoms of Ni, Mn, Co, M1, and M2.
[0040] The composite oxide particles of the present invention are preferably composed of a lithium nickel manganese cobalt-containing composite oxide (NMC) containing Ni, Mn, and Co as main transition metals. In this case, the composite oxide particles are preferably composed of a lithium nickel manganese cobalt-containing composite oxide (NMC) represented by the general formula (B): Li 1+u Ni x Mn y Co z M1 t It is preferable that the composition is O2 (-0.05≦u≦0.5, x+y+z+t=1, 0.3≦x≦0.7, 0.15≦y≦0.4, 0.15≦z≦0.4, 0≦t≦0.05, M1 is one or more additive elements selected from Mg, Al, Si, Ca, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W).
[0041] The composition of the positive electrode active material can be confirmed by, for example, inductively coupled plasma emission spectrometry or Rietveld analysis of parameters obtained by powder X-ray diffraction.
[0042] When the positive electrode active material of the present invention has a composition represented by the above general formula (A) or (B), it is of the layered rock salt type and has a hexagonal crystal structure.
[0043] (1-b) Particle structure In the positive electrode active material of the present invention, the composite oxide particles are composed of secondary particles formed by aggregation of a plurality of primary particles.
[0044] The secondary particles are The secondary particles One or more communication holes that communicate with the outer periphery of the Inside the secondary particleIt is preferable that the space exists in the space and has two or more spaces communicating with the communication hole.
[0045] The two or more spaces preferably communicate with the communication hole or with another space. The number of the communication holes is also preferably two or more.
[0046] When the composite oxide particles have such a secondary particle structure, it becomes possible to easily realize the particle properties of the positive electrode active material of the present invention, which will be described later.
[0047] If the pores in the outer periphery are not connected to the internal space, the space inside the particle is isolated, the electrolyte cannot penetrate sufficiently into the composite oxide particle (secondary particle), and a sufficient reaction field cannot be secured, so that the desired battery performance may not be fully achieved in a secondary battery using this positive electrode active material. Each of the two or more internal spaces can directly communicate with the pores in the outer periphery. Alternatively, they can communicate with the pores in the outer periphery via other pores.
[0048] This structure allows the electrolyte to penetrate sufficiently into the space inside the particle through the communicating holes on the outer periphery, making it possible to desorb and insert lithium not only on the surface of the particle but also inside the particle, ensuring a sufficient reaction field and making it possible to significantly reduce the internal resistance of the battery.
[0049] Therefore, when a lithium ion secondary battery is constructed by using a positive electrode active material having such a structure as a positive electrode material, it becomes possible to further improve the output characteristics.
[0050] (2) Covering layer The coating layer is present on at least a portion of the surface of the composite oxide particle and is composed of fine particles and / or a coating of a metal composite oxide of Li and a metal element M2 (M2 is one or more metal elements selected from Al, Ti, Zr, Nb, Mo, and W).
[0051] That is, in the positive electrode active material of the present invention, a coating layer consisting of fine particles and / or a coating of a metal composite oxide of Li and M2 is present on at least a portion of the surface of the composite oxide particle (or the secondary particle if the composite oxide particle is composed of secondary particles).
[0052] The coating layer of the metal composite oxide of Li and M2 has high lithium ion conductivity and is effective in promoting the movement of lithium ions. Therefore, by having a coating layer of the metal composite oxide of Li and M2 on the surface of the composite oxide particles, a Li conduction path is formed at the interface with the electrolyte, which reduces the reaction resistance (positive electrode resistance) of the positive electrode active material and improves its output characteristics.
[0053] That is, by reducing the positive electrode resistance, the voltage loss in the secondary battery is reduced, and the voltage actually applied to the load side is relatively high, so that high output can be obtained. In addition, by increasing the voltage applied to the load side, lithium is sufficiently inserted and removed from the positive electrode, so that the battery capacity is improved. Furthermore, by reducing the positive electrode resistance, the load on the positive electrode active material during charging and discharging is also reduced, so that the cycle characteristics can be improved.
[0054] The metal element M2 constituting the metal composite oxide with Li is one or more elements selected from the group consisting of Al, Ti, Zr, Nb, Mo, and W.
[0055] Among these, from the viewpoint of the effect of having the coating layer, M2 is preferably W, and the metal composite oxide constituting the coating layer is preferably lithium tungstate.
[0056] In order to enhance the effect of the coating layer, the ratio of M2 in the coating layer to the total number of Ni, Co, and Mn atoms in the composite oxide particles is Number of atoms(number of M2 atoms / (number of Ni atoms+number of Co atoms+number of Mn atoms)×100) is from 0.1 atomic % to 1.5 atomic %. It is preferably from 0.1 atomic % to 1.0 atomic %, more preferably from 0.2 atomic % to 0.9 atomic %, and even more preferably from 0.2 atomic % to 0.5 atomic %.
[0057] The composition of the coating layer can be confirmed by using inductively coupled plasma emission spectrometry, electron beam microanalyzer analysis, etc. The crystal structure of the coating layer can be confirmed by using powder X-ray diffraction or electron beam diffraction.
[0058] The coating layer can take the form of fine particles and / or a coating of a metal composite oxide of Li and M2. When the metal composite oxide of Li and M2 is composed of fine particles, the particle diameter of the fine particles is preferably in the range of 1 nm to 200 nm, and more preferably in the range of 1 nm to 100 nm. More preferred If the particle diameter of the fine particles is less than 1 nm, the fine particles may not have sufficient lithium ion conductivity. The upper limit of the particle diameter is about 200 nm, but if the particle diameter of the fine particles exceeds 100 nm, the formation of the coating by the fine particles becomes non-uniform, and the effect of reducing the reaction resistance tends to be insufficient, so it is preferable that 50% or more of the total number of the fine particles have a particle diameter in the range of 1 nm to 100 nm.
[0059] When the metal composite oxide of Li and M2 is formed by a coating, the thickness of the coating is preferably in the range of 1 nm to 200 nm. If the thickness is less than 1 nm, the coating may not have sufficient lithium ion conductivity. If the thickness exceeds 200 nm, the reaction area may decrease and the bulk resistance of the electrode may increase, and the effect of reducing the reaction resistance may not be sufficient.
[0060] Even when fine particles and a coating of a metal composite oxide of Li and M2 are mixed on the surface of the composite oxide particles, a high effect on the battery characteristics can be obtained.
[0061] The coating layer of the metal composite oxide of Li and M2 can be formed on the entire surface of the composite oxide particle. However, it is sufficient that the coating layer is formed on at least a part of the composite oxide particle, or the coating layer can be scattered on the surface of the composite oxide particle. Even in such a case, the presence of the coating layer can reduce the reaction resistance of the positive electrode active material. However, it is preferable that the coating layer of the metal composite oxide of Li and M2 is uniformly present on the surface of the composite oxide particle.
[0062] The properties of the coating layer can be determined, for example, by cross-sectional observation with a field emission scanning electron microscope, cross-sectional element mapping by EDX analysis with a scanning transmission electron microscope (STEM), or cross-sectional observation with a transmission ionization microscope.
[0063] (3) Particle size In the positive electrode active material of the present invention, the composite oxide particles having a coating layer have a 50% cumulative diameter d50 determined from particle size distribution measurements of 3.0 μm or more and 7.0 μm or less. composite oxide particles The 50% cumulative diameter d50 is preferably 4.0 μm or more and 6.5 μm or less, and more preferably 4.0 μm or more and 6.0 μm or less.
[0064] More specifically, the 50% cumulative diameter d50 is the particle size at which the cumulative volume calculated from the volume integrated value measured by a laser light diffraction scattering particle size analyzer is 50% of the total volume of all particles (the particle size at the point where the cumulative curve of the particle size distribution is 50% when the total volume is set to 100%).
[0065] If the d50 of the particles constituting the positive electrode active material is within the above range, not only can the battery capacity per unit volume of a secondary battery using this positive electrode active material be increased, but also the safety and output characteristics can be improved.
[0066] On the other hand, if the 50% cumulative diameter d50 is less than 3.0 μm, the packing property of the positive electrode active material decreases, and it may be difficult to increase the battery capacity per unit volume. If the 50% cumulative diameter d50 exceeds 7.0 μm, the reaction area of the positive electrode active material decreases, and the interface with the electrolyte decreases, so that it may be difficult to improve the output characteristics.
[0067] (4) BET specific surface area In the positive electrode active material of the present invention, the composite oxide particles having the coating layer have a particle size of 2.0 mm. 2 / g or more 5.0m 2 / g or less. The BET specific surface area is 2.5m 2 / g or more 4.6m 2 / g or less, and 3.0m 2 / g or more 4.4m 2 It is more preferable that the molecular weight is not more than 1 / g.
[0068] The BET specific surface area of the composite oxide particles having the coating layer is an index representing the particle properties (contact area with the electrolyte) of the positive electrode active material. Inside the secondary particle In the case where the secondary particle has two or more spaces communicating with the communicating pores, the BET specific surface area represents the surface area including the communicating pores (openings) present in the outer periphery of the secondary particle and the microcavities (spaces) inside the secondary particle.
[0069] The BET specific surface area is measured by the BET method using nitrogen gas adsorption.
[0070] BET specific surface area is 2.0m 2 If the BET specific surface area is less than 5.0 m / g, when a secondary battery is constructed using this positive electrode active material, the reaction area with the electrolyte cannot be sufficiently secured, and there is a possibility that the output characteristics will not be sufficiently improved. 2 If it exceeds 1 / g, the reaction area between the positive electrode active material and the electrolyte becomes too large, which may decrease the durability of the secondary battery.
[0071] (5) Tap density In the positive electrode active material of the present invention, the composite oxide particles having the coating layer have a density of 1.0 g / cm 3 More than 2.0g / cm 3 The tap density is 1.2 g / cm 3 It is preferable that the content is 1.3 g / cm or more. 3 More preferably, it is equal to or greater than this.
[0072] The tap density is an index of density that reflects the amount of solid domains inside a particle, for example, in a spherical particle.
[0073] Tap density is 1.0g / cm 3 If the tap density is less than 100%, the amount of solid domains in the composite oxide particles having the coating layer is small even if the BET specific surface area is increased, and the durability of the secondary battery may decrease. The secondary particles One or more communication holes that communicate with the outer periphery of the Inside the secondary particle and has two or more spaces communicating with the communicating holes, the upper limit under normal production conditions is 2.0 g / cm 3 It will be about that amount.
[0074] The tap density is the bulk density after a sample powder collected in a container is tapped 100 times based on JIS Z-2504, and can be measured using a shaking specific gravity measuring device.
[0075] (6) Oil absorption amount In the positive electrode active material of the present invention, the composite oxide particles having the coating layer have an oil absorption of 30 ml / 100 g or more and 60 ml / 100 g or less, preferably 35 ml / 100 g or more and 55 ml / 100 g or less, and more preferably 40 ml / 100 g or more and 50 ml / 100 g or less.
[0076] The oil absorption is an index representing the total volume of the space (total cavities) inside the secondary particles that constitute the composite oxide particles having the coating layer. Oil absorption amountIt can be determined by following the procedures described in "JIS K 6217-4:2008 (Carbon black for rubber - Basic properties - Part 4: Determination of oil absorption (including compressed samples))". However, since the operating process is complicated, the oil absorption is generally measured using an oil absorption measuring device that is marketed in accordance with the above JIS. The oil used for measurement is di-n-butyl phthalate (di-n-butyl phthalate, DBP), and the measurement result is calculated as the oil absorption per 100g of sample, so it is expressed in units of "ml / 100g".
[0077] If the oil absorption is less than 30 ml / 100 g, sufficient voids will not be formed, and it is possible that a sufficient BET specific surface area cannot be obtained.On the other hand, if the oil absorption exceeds 60 ml / 100 g, many voids will be structurally present inside the particles, resulting in a low bulk density and poor packing properties, and when a secondary battery is constructed, it is possible that a sufficient battery capacity per unit volume will not be obtained.
[0078] (7) Coefficient of variation of the concentration of added element M1 In the positive electrode active material of the present invention, the coefficient of variation (CV) indicating the variation in concentration of the additive element M1 within the primary particles constituting the composite oxide particles (secondary particles) is 1.5 or less, preferably 1.3 or less, and more preferably 1.2 or less.
[0079] The coefficient of variation of the concentration of the additional element M1 is an index showing the variation of the concentration of the additional element M1 throughout the primary particle including the grain interior and grain boundaries of the primary particle.
[0080] The variation coefficient of the concentration of the additive element M1 is obtained as follows. First, the positive electrode active material is processed into a thin slice using a focused ion beam device (FIB) or an ion milling device to expose the cross section of the secondary particle. Using a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM), two connected primary particles having a primary particle diameter in the range of 0.1 μm to 1.0 μm are targeted in the cross section of the secondary particle, and multiple locations of each of the two primary particles are irradiated with an electron beam, and the energy of the characteristic X-ray of the generated additive element M1 is analyzed with an energy dispersive X-ray analyzer (EDX) to determine the concentration of the additive element M1 at each location.
[0081] From the obtained data on the concentration of the additional element M1, the average concentration (μ) of the additional element M1 and the standard deviation (σ) of the concentration of the additional element M1 are obtained.
[0082] The coefficient of variation (CV) of the concentration of the additive element M1 is calculated by the formula: CV=σ / μ.
[0083] If the coefficient of variation (CV) of the concentration of the additive element M1 exceeds 1.5, the distribution of the additive element M1 in the primary particles and / or secondary particles will become biased, and in a secondary battery using this positive electrode active material, the battery performance such as the battery capacity and output characteristics may be impaired.
[0084] (8) Particle size distribution Although optional, in the positive electrode active material of the present invention, the index showing the spread of the particle size distribution of the composite oxide particles having the coating layer, [(d90-d10) / d50], is preferably 1.0 or less, more preferably 0.7 or less, and even more preferably 0.6 or less. A positive electrode active material made of particles having such a narrow particle size distribution has a small proportion of fine particles and coarse particles, and therefore a secondary battery using this has excellent safety, cycle characteristics, and output characteristics.
[0085] When [(d90-d10) / d50] exceeds 1.0, the ratio of fine particles and coarse particles in the positive electrode active material increases. For example, when the ratio of fine particles is high, the secondary battery is likely to generate heat due to local reactions of the fine particles, and not only does this lower safety, but the cycle characteristics may also be poor due to selective deterioration of the fine particles. In addition, when the ratio of coarse particles is high, the reaction area between the electrolyte and the positive electrode active material cannot be sufficiently secured, and the output characteristics may be poor.
[0086] In the case of industrial-scale production, it is not realistic to use a positive electrode active material with an excessively small [(d90-d10) / d50]. Therefore, in consideration of cost and productivity, it is preferable that the lower limit of [(d90-d10) / d50] is about 0.3.
[0087] The meaning and calculation method of d10 and d90 in the index showing the spread of particle size distribution [(d90-d10) / d50] are the same as those of d50 described above, where d90 is the particle size at which the cumulative volume of each particle, calculated from the smaller particle size side, is 90% of the total volume of all particles, and d10 is the particle size at which the cumulative volume of each particle, calculated from the smaller particle size side, is 10% of the total volume of all particles.
[0088] (9)d90 / d10 Although optional, in the positive electrode active material of the present invention, the ratio of the d90 value to the d10 value (d90 / d10) determined from the particle size distribution measurement value for the composite oxide particles having the coating layer is preferably 1.0 or more and 2.0 or less, and more preferably 1.2 or more and 1.8 or less.
[0089] If the d90 / d10 value of the composite oxide particles having a coating layer constituting the positive electrode active material is within this range, not only can the battery capacity per unit volume of the secondary battery using this positive electrode active material be increased, but also the safety and output characteristics can be improved. If the d90 / d10 value exceeds 2.0, the reaction area of the positive electrode active material decreases, and the interface with the electrolyte decreases, which may make it difficult to improve the output characteristics.
[0090] (10)Crystallite size determined from the X-ray diffraction pattern of the (003) plane Although optional, when the crystallite diameter of the primary particles of the composite oxide particles constituting the positive electrode active material of the present invention is determined by the Scherrer equation from the half-width of the peak of the (003) plane by X-ray diffraction, the crystallite diameter is preferably in the range of 300 Å to 1500 Å, more preferably in the range of 400 Å to 1300 Å, and even more preferably in the range of 700 Å to 1250 Å. A positive electrode active material having a crystallite diameter in such a range has extremely high crystallinity, and can reduce the positive electrode resistance of a secondary battery and improve its output characteristics.
[0091] If the crystallite diameter of the (003) plane is less than 300 Å, the primary particles are too fine and the pores between the primary particles in the positive electrode active material are too fine, making it difficult for the electrolyte to penetrate into the positive electrode active material, reducing the reaction area with the electrolyte and degrading the output characteristics of the secondary battery.If the crystallite diameter of the (003) plane exceeds 1500 Å, the primary particles become too coarse, drastically reducing the proportion of pores in the secondary particles and reducing the penetration paths for the electrolyte, reducing the reaction area with the electrolyte and degrading the output characteristics of the secondary battery.
[0092] 2. Manufacturing method of positive electrode active material for lithium-ion secondary batteries The positive electrode active material of the present invention is not limited by its production method so long as it has the above-mentioned composition, crystal structure, particle structure, and particle properties.
[0093] However, by producing the positive electrode active material of the present invention by the production method described below, it becomes possible to easily produce a positive electrode active material having the above-mentioned composition, crystal structure, particle structure, and particle properties.
[0094] Specifically, the positive electrode active material of the present invention is prepared by switching between an oxidizing atmosphere and a non-oxidizing atmosphere during a crystallization step to prepare a transition metal-containing composite hydroxide such as a nickel-manganese-cobalt-containing composite hydroxide, mixing the composite hydroxide or heat-treated particles of the composite hydroxide with a lithium compound, and calcining the resulting lithium mixture to obtain lithium transition metal-containing composite oxide particles. Lithium transition metal-containing composite oxide particles and the raw material for the coating layer M2 oxide By mixing and heat treating the mixture, a composite oxide of Li and M2 was formed. Lithium transition metal-containing composite oxide particles A positive electrode active material consisting of the above can be obtained.
[0095] Hereinafter, each step will be described in detail using as an example a case in which the composite oxide particles are lithium nickel manganese cobalt-containing composite oxide particles.
[0096] (1) Crystallization process Appropriate amounts of water, sodium hydroxide solution, and ammonia water are supplied to a reaction tank to prepare a pre-reaction aqueous solution adjusted to a pH value of 11 to 13 at a liquid temperature of 25°C and an ammonium ion concentration of 9 g / L to 15 g / L. Meanwhile, nickel sulfate, manganese sulfate, cobalt sulfate, and a compound of the added element M1 (sulfate, sodium salt, etc.) are dissolved in water so that the molar ratio of each metal element (Ni, Co, Mn, M1) satisfies the above formula (A), to obtain a raw material aqueous solution of 1.0 mol / L to 3.0 mol / L. preparation Alternatively, Nickel sulfate, Manganese sulfate and cobalt sulfate are dissolved in water so that the molar ratio of each metal element (Ni, Co, Mn) satisfies the above formula (A), and a raw material aqueous solution of 1.0 mol / L to 3.0 mol / L is obtained. preparationHowever, it is also possible to prepare a separate aqueous solution containing a compound of the additive element M1 and add it to the raw material aqueous solution so that the amount of the additive element M1 added satisfies the above formula (A).
[0097] Next, the raw material aqueous solution is supplied to the pre-reaction aqueous solution while blowing in a non-oxidizing atmosphere gas with an oxygen concentration of 2% by volume or less, such as argon gas or nitrogen, to perform nucleation. At this time, it is desirable to supply an aqueous sodium hydroxide solution and an aqueous ammonia solution at appropriate times to maintain the pH value and ammonium ion concentration of the aqueous solution for nucleation within the above-mentioned ranges.
[0098] After the nucleation is completed, an acid such as sulfuric acid is added to adjust the pH value to 10 to 12 at a liquid temperature of 25°C and lower than the pH value in the nucleation step, thereby forming an aqueous solution for particle growth. After it is confirmed that the pH value has reached a predetermined value, the raw material aqueous solution is supplied to grow the nuclei (particles) generated in the nucleation step. When an aqueous solution containing a compound of the additive element M1 is separately prepared, the aqueous solution containing the compound of the additive element M1 can be added only in the particle growth step or only at a specific stage of the particle growth step.
[0099] As the first stage of particle growth, crystallization is continued in a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less for a certain period of time from the start of the particle growth step while stirring with a stirrer.
[0100] In the second stage, while continuing to supply the raw material aqueous solution, a switching operation 1 is performed in which air or oxygen is circulated into the reaction tank using an aeration tube with a pore size in the range of 100 μm to 1 cm to adjust the reaction atmosphere to an oxidizing atmosphere with an oxygen concentration of 21% by volume or more. After the start of the switching operation 1, crystallization is performed while maintaining the oxidizing atmosphere and stirring with a stirrer for a certain period of time.
[0101] In the third stage, while continuing to supply the raw material aqueous solution, a switching operation 2 is performed in which a non-oxidizing gas is circulated in the reaction tank using an aeration tube to adjust the reaction atmosphere to a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less. After the start of the switching operation 2, crystallization is performed while maintaining the non-oxidizing atmosphere and stirring with a stirrer for a certain period of time.
[0102] In the fourth step, while continuing to supply the raw aqueous solution, a switching operation 3 is performed in which an oxidizing atmosphere gas is circulated in the reaction tank using an aeration tube to adjust the reaction atmosphere to an oxidizing atmosphere with an oxygen concentration of 21% by volume or more. After the start of the switching operation 3, crystallization is performed while maintaining the oxidizing atmosphere and stirring with a stirrer for a certain period of time.
[0103] In the fifth step, while continuing to supply the raw aqueous solution, a switching operation 4 is performed in which a non-oxidizing gas is circulated in the reaction tank using an aeration tube to adjust the reaction atmosphere to a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less. After the start of the switching operation 4, crystallization is performed while maintaining the non-oxidizing atmosphere and stirring with a stirrer for a certain period of time.
[0104] The time for each stage in the particle growth process is as follows: stage 2≦stage 4<stage 1≦stage 3≦stage 5. The crystallization time for the entire particle growth process is preferably within 8 hours.
[0105] Similarly, the particle growth step may be performed by switching operations 5 and 6 to provide a sixth stage in an oxidizing atmosphere and a seventh stage in a non-oxidizing atmosphere. Furthermore, the particle growth step may be performed by switching operations 7 and 8 to provide an eighth stage in an oxidizing atmosphere and a ninth stage in a non-oxidizing atmosphere. Furthermore, the particle growth step may be performed by additionally performing switching operations 9 and 10 to provide a tenth stage in an oxidizing atmosphere and an eleventh stage in a non-oxidizing atmosphere.
[0106] In these cases, the time for each stage in the particle growth process is: stage 2≦stage 4≦stage 6≦stage 8≦stage 10<stage 1≦stage 3≦stage 5≦stage 7≦stage 9≦stage 11.
[0107] After the crystallization is completed, the resulting product is washed with water, filtered and dried to obtain the desired nickel-cobalt-manganese-containing composite hydroxide particles.
[0108] In the particle growth step, it is desirable to supply an aqueous sodium hydroxide solution and an aqueous ammonia solution at appropriate times throughout the step, so as to maintain the pH value and the ammonium ion concentration of the aqueous solution for particle growth within the above-mentioned ranges.
[0109] The composite hydroxide particles obtained by such a crystallization process have a particle structure in which low-density layers and high-density layers are alternately laminated around a high-density center. By using the composite hydroxide particles having such a particle structure as a precursor, The secondary particles are composed of aggregates of primary particles. One or more communication holes that communicate with the outer periphery of the Inside the secondary particle Thus, composite oxide particles having a particle structure having two or more spaces which are in communication with the communicating pores can be easily obtained.
[0110] (2)Mixing process The mixing step is a step of mixing the above-mentioned composite hydroxide particles or heat-treated particles obtained by subjecting the composite hydroxide particles to a heat treatment with a lithium compound to obtain a lithium mixture.
[0111] In the mixing step, the composite hydroxide particles and the lithium compound are mixed so that the ratio (Li / Me) of the sum of the atomic numbers of metal atoms other than Li in the lithium mixture, specifically Ni, Mn, Co, and the additive element M1 (Me) to the atomic number of Li (Li) is 0.95 to 1.5, preferably 1.0 to 1.5, more preferably 1.0 to 1.35, and even more preferably 1.0 to 1.2. That is, since Li / Me does not change before and after the baking step, it is necessary to mix the composite hydroxide and the lithium compound so that the Li / Me in the mixing step becomes the Li / Me of the target positive electrode active material.
[0112] The lithium compound used in the mixing step is not particularly limited, but it is preferable to use lithium hydroxide, lithium nitrate, lithium carbonate, or a mixture thereof in terms of availability. In particular, it is preferable to use lithium hydroxide or lithium carbonate in terms of ease of handling and stability of quality.
[0113] For mixing, a general mixer such as a shaker mixer, a Loedige mixer, a Julia mixer, or a V blender can be used.
[0114] (3) Calcination process When lithium hydroxide or lithium carbonate is used as the lithium compound, a calcination step can be performed after the mixing step and before the calcination step, in which the lithium mixture is calcined at a temperature lower than the calcination temperature described below and between 350° C. and 800° C., preferably between 450° C. and 750° C. This allows Li to be sufficiently diffused in the composite hydroxide particles, and more uniform composite oxide particles can be obtained.
[0115] The holding time at the above temperature is preferably 1 hour to 10 hours, more preferably 3 hours to 6 hours. The atmosphere in the calcination step is preferably an oxidizing atmosphere, similar to the firing step described below, and more preferably an atmosphere with an oxygen concentration of 18 volume % to 100 volume %.
[0116] (4) Firing process The calcination step is a step in which the lithium mixture obtained in the mixing step is calcined under predetermined conditions to diffuse Li into the composite hydroxide and cause a reaction, thereby obtaining composite oxide particles.
[0117] The furnace used in the firing step is not particularly limited, and may be any furnace capable of heating the lithium mixture in air or oxygen flow. However, from the viewpoint of maintaining a uniform atmosphere in the furnace, an electric furnace that does not generate gas is preferred, and either a batch-type or continuous-type electric furnace can be suitably used. This point is the same for the furnaces used in the heat treatment step and the calcination step.
[0118] a) Firing temperature The calcination temperature of the lithium mixture is set to 720°C or more and 980°C or less. If the calcination temperature is less than 720°C, the composite hydroxide particles and Li do not react sufficiently, and excess Li or unreacted composite hydroxide remains, or the crystallinity of the resulting positive electrode active material becomes insufficient. On the other hand, if the calcination temperature exceeds 980°C, the interconnected holes and spaces in the composite oxide particles are crushed, which may lead to a decrease in the BET specific surface area and oil absorption of the finally obtained positive electrode active material, and an increase in tap density. In addition, the particles of the positive electrode active material are sintered violently, causing abnormal grain growth, and increasing the proportion of amorphous coarse particles.
[0119] By controlling the firing temperature, it is possible to control the BET specific surface area, oil absorption, tap density, and 50% cumulative diameter d50 obtained from particle size distribution measurement values of the positive electrode active material. From the viewpoint of controlling the BET specific surface area, oil absorption, tap density, and 50% cumulative diameter d50 obtained from particle size distribution measurement values of the positive electrode active material, it is preferable to set the firing temperature of the lithium mixture to 730°C or higher and 970°C or lower, and more preferably to set it to 750°C or higher and 970°C or lower.
[0120] The heating rate in the calcination step is preferably set to 1° C. / min to 10° C. / min, more preferably 3° C. / min to 8° C. / min. Furthermore, during the calcination step, at a temperature near the melting point of the lithium compound, the heating rate is lowered to 0.3° C. / min to 6° C. / min, more preferably. This allows the composite hydroxide particles and the lithium compound to react more uniformly.
[0121] b) Baking time During the firing time, the holding time at the above firing temperature is preferably at least 2 hours, and more preferably 3 hours to 20 hours. If the holding time at the firing temperature is less than 2 hours, Li may not be sufficiently diffused into the composite oxide particles, and excess Li or unreacted composite oxide particles may remain, or the crystallinity of the resulting positive electrode active material may be insufficient.
[0122] c) Firing atmosphere The atmosphere during firing is preferably an oxidizing atmosphere, more preferably an atmosphere with an oxygen concentration of 18% by volume or more and 100% by volume or less, and even more preferably an atmosphere with an oxygen concentration of 50% by volume or more and 100% by volume or less. A mixed atmosphere of oxygen and an inert gas with the above oxygen concentration is particularly preferable. That is, firing is preferably performed in air or in an oxygen stream. If the oxygen concentration is less than 18% by volume, the crystallinity of the positive electrode active material may be insufficient.
[0123] (5) Crushing process The composite oxide particles (secondary particles) obtained by the firing process may be aggregated or lightly sintered. In such a case, it is preferable to crush the aggregates or sintered bodies. This allows the average particle size and particle size distribution of the obtained positive electrode active material to be adjusted to a suitable range. Note that crushing refers to an operation of applying mechanical energy to aggregates consisting of multiple secondary particles generated by sintering necking between particles during firing, separating the secondary particles themselves with almost no destruction, and loosening the aggregates.
[0124] As a crushing method, known means can be used, for example, a pin mill, a hammer mill, etc. In this case, it is preferable to control the crushing force within an appropriate range so as not to destroy the secondary particles themselves.
[0125] As described above, by adjusting the firing conditions, it is possible to control the BET specific surface area, oil absorption, tap density, and 50% cumulative diameter d50 obtained from particle size distribution measurements of the positive electrode active material, and ultimately, it is possible to easily obtain the positive electrode active material of the present invention having predetermined particle properties.
[0126] (6) Covering process In the coating step, the composite oxide particles are mixed and stirred with an oxide of one or more metals selected from Al, Ti, Zr, Nb, Mo, and W, which is the metal element M2 used as the raw material for the coating layer, while being sprayed with an aqueous solution or an acidic aqueous solution containing ammonium or the like, and then a heat treatment is performed. By such a treatment, a coating layer consisting of fine particles and / or a coating of a metal composite oxide of Li and M2 is formed on at least a part of the surface of the composite oxide particles.
[0127] A general mixer can be used for mixing and stirring. For example, a shaker mixer, a drum mixer, a vacuum mixing dryer, etc. can be used. Stirring is performed under conditions that allow the composite oxide particles and the oxide of M2 to be mixed sufficiently to the extent that the composite oxide particles are not destroyed. However, simply stirring the composite oxide particles and the oxide of M2 makes it difficult for the reaction between the oxide of M2, which is the raw material of the coating layer, and the lithium compound present on the surface of the composite oxide particles to proceed, so it is preferable to stir while appropriately spraying water, an alkaline aqueous solution, or an acidic aqueous solution.
[0128] If the stirring is carried out at room temperature, the oxide of M2 and the lithium compound do not react sufficiently, so it is preferable to carry out a heat treatment at a temperature of 100° C. or higher and 250° C. or lower for 1 hour or more during or after the stirring.
[0129] As described above, the coating layer is composed of fine particles and / or a coating of the metal composite oxide of Li and M2. Whether fine particles or a coating is formed, or whether both are formed, is determined by the moisture content of the powder after dehydration. Therefore, it is possible to obtain a desired coating layer structure according to the composition of the metal composite oxide of Li and M2, the configuration of the coating layer in advance, and the moisture content of the powder after dehydration.
[0130] The amount of metal element M2 contained in the coating layer is preferably 0.1 atomic % or more and 1.5 atomic % or less with respect to the total number of atoms of Ni, Co, and Mn contained in the composite oxide powder to be mixed. This allows both high output characteristics and durability to be achieved. If the amount of M2 contained in the coating layer is less than 0.1 atomic %, the effect of improving the output characteristics may not be sufficiently obtained. If the amount of M2 contained in the coating layer exceeds 1.5 atomic %, the amount of lithium composite oxide becomes too large, which may inhibit Li conduction between the positive electrode active material and the electrolyte, resulting in a decrease in battery performance. It is more preferable that the amount of M2 contained in the coating layer is 0.15 atomic % or more and 1.4 atomic % or less with respect to the total number of atoms of Ni, Co, and Mn contained in the composite oxide powder.
[0131] 3. Lithium-ion secondary battery The lithium ion secondary battery of the present invention can have the same configuration as a general non-aqueous electrolyte secondary battery, including components such as a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. Alternatively, the lithium ion secondary battery of the present invention can have the same configuration as a general solid electrolyte secondary battery, including components such as a positive electrode, a negative electrode, and a solid electrolyte. That is, the present invention can be widely applied to a non-aqueous electrolyte secondary battery to an all-solid-state lithium ion secondary battery, as long as the secondary battery is charged and discharged by desorption and insertion of lithium ions. Note that the embodiments described below are merely examples, and the present invention can be applied to lithium ion secondary batteries in various forms that have been modified and improved based on the embodiments described in this specification.
[0132] (1) Components a) Positive electrode Using the positive electrode active material of the present invention, a positive electrode of a lithium ion secondary battery is produced, for example, as follows.
[0133] First, the conductive material and the binder are mixed with the positive electrode active material of the present invention, and if necessary, activated carbon, a solvent for viscosity adjustment, etc. are added, and these are kneaded to prepare a positive electrode composite paste. At that time, the mixing ratio of each in the positive electrode composite paste is also an important factor that determines the performance of the lithium ion secondary battery. For example, when the solid content of the positive electrode composite excluding the solvent is 100 parts by mass, the content of the positive electrode active material can be 60 parts by mass or more and 95 parts by mass or less, the content of the conductive material can be 1 part by mass or more and 20 parts by mass or less, and the content of the binder can be 1 part by mass or more and 20 parts by mass or less, as in the case of the positive electrode of a general lithium ion secondary battery.
[0134] The obtained positive electrode composite paste is applied to the surface of a current collector made of, for example, aluminum foil, and dried to evaporate the solvent. If necessary, pressure may be applied by a roll press or the like to increase the electrode density. In this way, a sheet-shaped positive electrode can be produced. The sheet-shaped positive electrode can be cut to an appropriate size according to the intended battery and used to produce the battery. The method for producing the positive electrode is not limited to the above-mentioned example, and other methods may be used.
[0135] As the conductive material, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.) and carbon black-based materials such as acetylene black and ketjen black can be used.
[0136] The binder serves to bind the active material particles together, and may be, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resin, or polyacrylic acid.
[0137] In addition, if necessary, a solvent for dispersing the positive electrode active material, conductive material, and activated carbon and dissolving the binder can be added to the positive electrode mixture. Specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent. Activated carbon can also be added to the positive electrode mixture to increase the electric double layer capacity.
[0138] b) Negative electrode The negative electrode can be made of metallic lithium, a lithium alloy, etc. Also, a negative electrode active material capable of absorbing and desorbing lithium ions can be mixed with a binder, and an appropriate solvent can be added to make a paste-like negative electrode mixture, which can be applied to the surface of a metal foil current collector such as copper, dried, and compressed to increase the electrode density as necessary.
[0139] As the negative electrode active material, for example, a material containing lithium such as metallic lithium or a lithium alloy, natural graphite or artificial graphite capable of absorbing and desorbing lithium ions, a fired organic compound such as phenolic resin, or a powder of a carbon material such as coke can be used. In this case, as with the positive electrode, a fluorine-containing resin such as PVDF can be used as the negative electrode binder, and an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent for dispersing these negative electrode active materials and binders.
[0140] c) Separator The separator is sandwiched between the positive electrode and the negative electrode in the lithium ion secondary battery, and has the function of separating the positive electrode and the negative electrode and retaining the electrolyte. As such a separator, for example, a thin membrane such as polyethylene or polypropylene having a large number of fine pores can be used, but there is no particular limitation as long as it has the above function. In addition, a solid electrolyte can also be used.
[0141] d) electrolytes The nonaqueous electrolyte used in the nonaqueous electrolyte secondary battery is, for example, a nonaqueous electrolytic solution obtained by dissolving a lithium salt, which serves as a supporting salt, in an organic solvent.
[0142] The organic solvent used in the nonaqueous electrolyte may be one selected from the following: cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; and phosphorus compounds such as triethyl phosphate and trioctyl phosphate. These may be used alone or in combination of two or more.
[0143] As the supporting salt, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, and composite salts of these can be used.
[0144] The non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0145] The solid electrolyte used in solid electrolyte secondary batteries such as all-solid-state lithium ion secondary batteries has the property of being able to withstand high voltages. Solid electrolytes include inorganic solid electrolytes and organic solid electrolytes.
[0146] The oxide solid electrolyte may be an oxide that contains oxygen (O) and has lithium ion conductivity and electronic insulation properties, such as Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li3PO4, Li3PO4N X , LiBON X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≦X≦1), Li 1+X Al X Ge 2-X(PO4)3(0≦X≦1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≦X≦2 / 3), Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 S 0.6 P 0.4 O4 etc. can be used.
[0147] As the sulfide solid electrolyte, sulfides containing sulfur (S) and having lithium ion conductivity and electronic insulation, such as Li2S-SiS2, Li2S-P2S5, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc. can be used.
[0148] As the inorganic solid electrolyte other than the oxide solid electrolyte and the sulfide solid electrolyte, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. can be used.
[0149] As the organic solid electrolyte, a polymeric compound exhibiting ion conductivity can be used. For example, polyethylene oxide, polypropylene oxide, copolymers thereof, etc. can be used. The organic solid electrolyte can also contain a supporting salt (lithium salt).
[0150] When a solid electrolyte is used, the solid electrolyte can be mixed into the positive electrode material in order to ensure contact between the electrolyte and the positive electrode active material.
[0151] (2) Structure of lithium-ion secondary battery The configuration of the lithium ion secondary battery is not particularly limited, and may be a non-aqueous electrolyte secondary battery having a positive electrode, a negative electrode, a separator, a non-aqueous electrolyte, etc., or a solid electrolyte secondary battery having a positive electrode, a negative electrode, a solid electrolyte, etc. The shape of the secondary battery is not particularly limited, and may be a cylindrical shape, a laminated shape, or various other shapes.
[0152] In the case of a non-aqueous electrolyte secondary battery, for example, a positive electrode and a negative electrode are laminated with a separator therebetween to form an electrode body, the obtained electrode body is impregnated with a non-aqueous electrolyte, the positive electrode current collector and a positive electrode terminal connected to the outside, and the negative electrode current collector and a negative electrode terminal connected to the outside are connected using a current collecting lead or the like, and the battery is sealed in a battery case to complete a lithium ion secondary battery.
[0153] (3) Characteristics of lithium-ion secondary batteries As described above, the lithium ion secondary battery of the present invention uses the positive electrode active material of the present invention as a positive electrode material, and therefore has excellent output characteristics and durability characteristics.
[0154] (4) Uses of lithium-ion secondary batteries As described above, the lithium ion secondary battery of the present invention has excellent output characteristics and durability characteristics, and can be suitably used as a power source for power tools and eco-friendly automobiles, which require a high level of these characteristics. EXAMPLES
[0155] The present invention will be described in detail below with reference to examples and comparative examples. Throughout the nucleation step and the particle growth step, the pH value of the reaction solution was measured by a pH controller, and the supply amount of the sodium hydroxide solution was adjusted based on the measured value, thereby controlling the fluctuation width of the pH value of the reaction solution in each step within the range of ±0.2.
[0156] Example 1 a) Preparation of composite hydroxides [Nucleation process] First, 17 L of water was put into the reaction tank and the temperature in the tank was set to 40° C. while stirring. At this time, nitrogen gas was circulated in the reaction tank for 1 hour, and the reaction atmosphere was made a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less. Next, an appropriate amount of 25% by mass aqueous sodium hydroxide solution and 25% by mass aqueous ammonia were supplied into the reaction tank, and the pH value was adjusted to 12.6 at a liquid temperature of 25° C. and the ammonium ion concentration was adjusted to 10 g / L to form a pre-reaction aqueous solution.
[0157] At the same time, nickel sulfate, manganese sulfate, cobalt sulfate, and aluminum sulfate were mixed in a mixture with a molar ratio of each metal element of Ni:Co:Mn:Al=5.0:2.0:3.0: 0.3 The raw material solution was dissolved in water so as to obtain a concentration of 2 mol / L.
[0158] Next, the raw water solution was fed to the pre-reaction aqueous solution at 115 ml / min. Aqueous solution for nucleation During this process, a 25% by mass aqueous solution of sodium hydroxide and a 25% by mass aqueous solution of ammonia were supplied at appropriate times to maintain the pH value and ammonium ion concentration of the aqueous solution for nucleation within the above-mentioned ranges.
[0159] [Particle growth process] After the nucleation was completed, the supply of all aqueous solutions was stopped temporarily, and sulfuric acid was added to adjust the pH value to 11.0 at a liquid temperature of 25°C, forming an aqueous solution for particle growth. After it was confirmed that the pH value had reached the specified value, the raw material aqueous solution was supplied at a constant rate of 100 ml / min, the same as in the nucleation process, to grow the nuclei (particles) generated in the nucleation process.
[0160] In the first stage, crystallization was continued for 35 minutes in a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less from the start of the particle growth step while stirring with a stirrer.
[0161] In the second stage, while continuing to supply the raw material aqueous solution, air was circulated in the reaction tank using a SUS air diffuser with a pore size of 1.0 mm, and the reaction atmosphere was adjusted to an oxidizing atmosphere with an oxygen concentration of 21% by volume (switching operation 1). After the start of switching operation 1, crystallization was carried out for 20 minutes while stirring with a stirrer.
[0162] In the third stage, while continuing to supply the raw material aqueous solution, nitrogen was circulated in the reaction tank using an aeration tube, and the reaction atmosphere was adjusted to a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less (switching operation 2). After the start of switching operation 2, crystallization was carried out for 65 minutes while stirring with a stirrer.
[0163] In the fourth step, air is circulated into the reaction tank using an air diffuser while continuing to supply the raw solution. The reaction atmosphere is The oxygen concentration was adjusted to 21% by volume to create an oxidizing atmosphere (switching operation 3). After the start of switching operation 3, crystallization was carried out for 40 minutes while stirring with a stirrer.
[0164] In the fifth step, while continuing to supply the raw aqueous solution, nitrogen was circulated in the reaction tank using an aeration tube, and the reaction atmosphere was adjusted to a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less (switching operation 4). After the start of switching operation 4, crystallization was carried out for 110 minutes while stirring using a stirrer.
[0165] Thereafter, the supply of all aqueous solutions including the raw material aqueous solution was stopped to terminate the particle growth process. The resulting product was washed with water, filtered and dried to obtain composite hydroxide particles.
[0166] In the particle growth step, a 25% by mass aqueous sodium hydroxide solution and a 25% by mass aqueous ammonia solution were appropriately supplied throughout the step to maintain the pH value and ammonium ion concentration of the aqueous solution for particle growth within the above-mentioned ranges.
[0167] b) Preparation of positive electrode active material The obtained composite hydroxide was thoroughly mixed with lithium hydroxide using a shaker mixer so that the Li / Me ratio was 1.10, to obtain a lithium mixture (mixing step).
[0168] This lithium mixture was heated to 920° C. at a heating rate of 1.3° C. / min in an oxygen atmosphere (oxygen concentration: 100% by volume), sintered by maintaining at this temperature for 3 hours, and then cooled to room temperature (sintering step).
[0169] In order to eliminate aggregation or slight sintering of the obtained lithium transition metal-containing composite oxide particles, this positive electrode active material was crushed (crushing step).
[0170] Then, tungsten oxide in an amount equivalent to 0.8% by mass relative to the mass of the lithium transition metal composite oxide particles was thoroughly mixed with the composite oxide particles using a mixer, and water (pure water) in an amount equivalent to 10% by mass relative to the mass of the composite oxide particles was sprayed onto the surfaces of the composite oxide particles, followed by heat treatment at 150°C for 1 hour to perform surface treatment (coating process).
[0171] c) Evaluation of positive electrode active material [composition] After the crushing process and before the coating process, the composition of the composite oxide particles before coating was analyzed using an ICP emission spectrometer (Shimadzu Corporation, ICPE-9000). 1.1 Ni 0.480 Mn 0.300 Co 0.188 Al 0.032 It was O2.
[0172] [Particle size distribution] A laser light diffraction / scattering particle size analyzer (Microtrack MT3300EXII, manufactured by Microtrack-Bell Corporation) was used to measure the 50% cumulative diameter d50, 10% cumulative diameter d10, and 90% cumulative diameter d90 obtained from the particle size distribution measurements of the positive electrode active material (composite oxide particles after coating).
[0173] [BET specific surface area and tap density] The BET specific surface area of the positive electrode active material (composite oxide particles after coating) was measured using a flow type gas adsorption specific surface area measurement device (Maxsorb 1200 series, manufactured by Mountec Co., Ltd.), and the tap density of the positive electrode active material (composite oxide particles after coating) was measured using a tapping machine (Kuramochi Scientific Instruments Manufacturing Co., Ltd., KRS-406).
[0174] [Oil absorption amount] The oil absorption of the positive electrode active material (coated composite oxide particles) was measured using an absorption measuring device (S-500, manufactured by Asahi Research Institute Co., Ltd.) conforming to "JIS K 6217-4:2008".
[0175] [Particle structure] A part of the positive electrode active material was embedded in a resin, processed with a cross-section polisher (IB-19530CP, manufactured by JEOL Ltd.) to be in a state where a cross section could be observed, and then observed with a SEM (FE-SEM: JSM-6360LA, manufactured by JEOL Ltd.). As shown in Fig. 1, the positive electrode active material of the present invention is formed of secondary particles formed by agglomeration of a plurality of primary particles, has about 10 communicating holes on the outer periphery of the secondary particle, has about 15 spaces inside the secondary particle, and has a space between the communicating holes on the outer periphery and the inside. space section I confirmed that it is connected.
[0176] [Coefficient of variation] An ion milling device (Cryo-ion slicer, IB-09060CIS, manufactured by JEOL Ltd.) was used to process the cross section of the positive electrode active material (secondary particles) into a thin slice. Using a TEM (JEM-ARM200F, manufactured by JEOL Ltd.), an electron beam was irradiated to a total of 12 points arbitrarily selected from the entire primary particle, including the grain interior and grain boundaries, aiming at approximately 0.5 μm primary particles (two connected particles sandwiching a grain boundary) in the cross section of the secondary particles, and the energy and number of occurrences of the characteristic X-rays generated were measured. The measured values were analyzed by EDX (NSS, manufactured by Thermo Fisher Scientific Co., Ltd.) to obtain a TEM image. UsingThe analysis was performed to determine the average Al concentration (μ), standard deviation (σ) of the Al concentration, and coefficient of variation (CV) of the Al concentration in each primary particle. Table 1 shows the results of the measurement of the Al concentration of the obtained primary particles by TEM-EDX analysis.
[0177] As a result, the average Al concentration (μ) was 1.0, the standard deviation (σ) of the Al concentration was 1.1, and the coefficient of variation (CV) of the Al concentration was 1.1.
[0178] [Table 1] [Identification of the coating layer] The coating layer was identified by synchrotron radiation powder X-ray diffraction measurement and electron diffraction using a transmission electron microscope using BL19B2 at SPring8. It was confirmed that the coating layer was composed of lithium tungstate. The W content was 0.4 atomic %.
[0179] d) Preparation of secondary batteries A 2032-type coin battery 10 was produced as shown in Fig. 3. Specifically, 52.5 mg of the positive electrode active material obtained as described above, 15 mg of acetylene black, and 7.5 mg of PTFE were mixed and pressed at a pressure of 100 MPa to produce a positive electrode 1 with a diameter of 11 mm and a thickness of 100 µm.
[0180] Next, a 2032-type coin battery was produced using this positive electrode 12 in a glove box in an Ar atmosphere with a dew point controlled at -60°C. A lithium metal with a diameter of 14 mm and a thickness of 1 mm was used for the negative electrode 2 of the 2032-type coin battery, and an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiClO4 as a supporting electrolyte (manufactured by Ube Industries, Ltd.) was used for the non-aqueous electrolyte. In addition, a polyethylene porous film with a thickness of 25 μm was used for the separator 3. In this way, a 2032-type coin battery 10 having a gasket 4 and a wave washer 5, a positive electrode can 6, and a negative electrode can 7 was assembled.
[0181] e) Battery evaluation [Positive electrode resistance] The positive electrode resistance was measured using the impedance measurement method. A 2032 coin cell was charged at 3.8 V and measured by the AC impedance method using a frequency response analyzer and a potentiogalvanostat (Solartron, 1255B), obtaining the impedance spectrum shown in Figure 4. The impedance spectrum obtained showed two semicircles in the high frequency and intermediate frequency regions, and a straight line in the low frequency region, so the positive electrode interface resistance was analyzed using the equivalent circuit shown in Figure 5. Here, Rs is the bulk resistance, R1 is the positive electrode film resistance, and R ct indicates the electrolyte / positive electrode interface resistance, W indicates the Warburg component, and CPE1 and CPE2 indicate constant phase elements. The positive electrode interface resistance is based on the positive electrode active material of Comparative Example 1 described later, and the resistance reduction rate relative to this is shown.
[0182] The characteristics of the obtained positive electrode active material and the characteristics of the obtained lithium ion secondary battery are shown in Table 2. Note that, regarding these, the same is shown in Table 2 for Examples 2 to 7 and Comparative Examples 1 to 6.
[0183] Example 2 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that the lithium mixture was heated to 890° C. and calcined by maintaining it at this temperature for 3 hours.
[0184] Example 3 Except for changing the mass of tungsten oxide to be treated in the coating step to 0.4 mass%, a positive electrode active material was obtained and evaluated in the same manner as in Example 2. The W content was 0.2 atomic %.
[0185] Example 4 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that aluminum sulfate was not added in the manufacturing process of the composite hydroxide, and aluminum oxide was added and calcined in the manufacturing process of the positive electrode active material.
[0186] Example 5 Except for changing the mass of tungsten oxide to be treated in the coating step to 2.4 mass%, a positive electrode active material was obtained and evaluated in the same manner as in Example 2. The W content was 1.2 atomic %.
[0187] Example 6 Except for changing the tungsten oxide to be treated in the coating step to molybdenum oxide, a positive electrode active material was obtained and evaluated in the same manner as in Example 2. The Mo content was 0.5 atomic %.
[0188] Example 7 The same procedure as in Example 2 was repeated, except that the tungsten oxide used in the coating process was changed to niobium oxide. positive electrode active material The Nb content was 0.4 atomic %.
[0189] Comparative Example 1 In the crystallization process, crystallization was performed in an oxidizing atmosphere with an oxygen concentration of 21% by volume up to switching operation 1 between the nucleation process and the particle growth process, and the atmosphere was adjusted to a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less from that point on to obtain a composite hydroxide. A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that the composite hydroxide was obtained. Figure 2 shows the particle structure of the positive electrode active material obtained. The positive electrode active material is formed from secondary particles formed by agglomeration of multiple primary particles, and has one communicating hole on the outer periphery of the secondary particle, one space inside the secondary particle, and a space between the communicating hole on the outer periphery and the internal space section It was confirmed that the structure is a hollow structure in which the above is connected.
[0190] Comparative Example 2 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that aluminum sulfate was not added in the manufacturing process of the composite hydroxide, aluminum oxide was added in the manufacturing process of the positive electrode active material, and the firing temperature was 870°C.
[0191] Comparative Example 3 In the crystallization step, the crystallization time in each stage of the particle growth step was adjusted to 35 minutes for the first stage, 40 minutes for the second stage, 45 minutes for the third stage, 60 minutes for the fourth stage, and 90 minutes for the fifth stage, in the same manner as in Example 1. positive electrode active material The results were obtained and evaluated.
[0192] Comparative Example 4 In the crystallization step, the crystallization time in each stage of the particle growth step was adjusted to 35 minutes for the first stage, 10 minutes for the second stage, 75 minutes for the third stage, 30 minutes for the fourth stage, and 120 minutes for the fifth stage, in the same manner as in Example 1. positive electrode active material The results were obtained and evaluated.
[0193] Comparative Example 5 The same procedure as in Example 1 was repeated except that the coating treatment step was not performed. positive electrode active material The results were obtained and evaluated.
[0194] Comparative Example 6 Except for changing the mass of tungsten oxide to be treated in the coating step to 3.2 mass%, a positive electrode active material was obtained and evaluated in the same manner as in Example 2. The W content was 1.6 atomic %.
[0195] [Table 2] It was confirmed that, when any of the positive electrode active materials of Examples 1 to 7 within the scope of the embodiment of the present invention were used in a lithium ion secondary battery, the positive electrode resistance was reduced and the output characteristics were improved in comparison with Comparative Examples 1 to 6. [Explanation of symbols]
[0196] 1 Positive electrode (electrode for evaluation) 2 negative electrode 3. Separator 4 Gasket 5 Wave Washer 6 Positive electrode can 7 Anode can 10 Coin cell battery
Claims
1. General formula (A): Li 1+u Ni x Mn y Co z M1 t O 2 (wherein, −0.05≦u≦0.50, x+y+z+t=1, 0.3≦x≦0.9, 0≦y≦0.5, 0≦z≦0.5, 0.001≦t≦0.05, and M1 is one or more additive elements selected from Mg, Al, Si, Ca, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W), and lithium transition metal-containing composite oxide particles having a crystal structure of a layered rock salt structure, a coating layer present on at least a portion of the surface of the lithium transition metal-containing composite oxide particle and consisting of fine particles and / or a coating of a metal composite oxide of Li and a metal element M2 (M2 is one or more metal elements selected from Al, Ti, Zr, Nb, Mo, and W); Equipped with The lithium transition metal-containing composite oxide particles are composed of secondary particles formed by agglomeration of primary particles, the secondary particle has one or more communicating holes communicating with the outer periphery of the secondary particle, and two or more spaces present inside the secondary particle and communicating with the communicating holes, The lithium transition metal-containing composite oxide particles having the coating layer have a 50% cumulative diameter d50 and a 2.0m cumulative diameter d50 calculated from a particle size distribution measurement value of 3.0 μm or more and 7.0 μm or less. 2 / g or more 5.0m 2 / g or less BET specific surface area, 1.0 g / cm 3 2.0g / cm or more 3 and an oil absorption of 30 ml / 100 g or more and 60 ml / 100 g or less, Among the primary particles, for each of a plurality of primary particles having a primary particle diameter in the range of 0.1 μm or more and 1.0 μm or less, the concentration of the additional element M1 is measured at a plurality of locations by cross-sectional STEM or TEM-EDX analysis, and a coefficient of variation, which is a value obtained by dividing the standard deviation of the concentration of the additional element M1 by the average concentration, is calculated, and the coefficient of variation is 1.5 or less, and The amount of M2 contained in the coating layer is 0.1 atomic % or more and 1.5 atomic % or less with respect to the total number of Ni, Mn, and Co atoms contained in the lithium transition metal-containing composite oxide particles. Positive electrode active material for lithium-ion secondary batteries.
2. 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein the 50% cumulative diameter d50 of the lithium transition metal-containing composite oxide particles having the coating layer is 4.0 μm or more and 6.0 μm or less.
3. 3. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein [(d90-d10) / d50] (where d10 is the 10% cumulative diameter obtained from the particle size distribution measurement value, and d90 is the 90% cumulative diameter obtained from the particle size distribution measurement value), which is an index showing the spread of the particle size distribution of the lithium transition metal-containing composite oxide particles provided with the coating layer, is 1.0 or less.
4. The lithium-ion secondary battery positive electrode active material according to any one of claims 1 to 3, wherein the lithium transition metal-containing composite oxide particles having the coating layer have a d90 / d10 value (wherein d10 is the 10% cumulative diameter obtained from particle size distribution measurement values, and d90 is the 90% cumulative diameter obtained from particle size distribution measurement values) of 1.0 or more and 2.0 or less.
5. The additive element M1 is at least one selected from the group consisting of Mg, Al, Si, Ti, Zr, Nb, Mo, and W. The positive electrode active material for lithium ion secondary batteries according to any one of claims 1 to 4.
6. The positive electrode active material for a lithium ion secondary battery according to claim 5 , wherein the additional element M1 is made of Al.
7. The positive electrode active material for lithium ion secondary batteries according to any one of claims 1 to 6, wherein M2 contained in the coating layer is W.
8. 8. The positive electrode active material for a lithium ion secondary battery according to claim 7, wherein the metal composite oxide is lithium tungstate.
9. A lithium ion secondary battery comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, or a positive electrode, a negative electrode, and a solid electrolyte, and using the positive electrode active material for lithium ion secondary batteries according to any one of claims 1 to 8 as a positive electrode active material used in the positive electrode.
Citation Information
Patent Citations
Manganese composite hydroxide particle, positive pole active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery, and method for producing them
JP2012246199A
Transition metal composite hydroxide particle, manufacturing method for the same, positive electrode active material for nonaqueous electrolyte secondary battery, manufacturing method for the same and nonaqueous electrolyte secondary battery
JP2017016753A
Nonaqueous electrolyte secondary battery
JP2017091664A
Transition metal-containing composite hydroxide particle and production method of the same, and positive electrode active substance for non-aqueous electrolyte secondary cell and production method of the same
JP2018104276A
Nickel-manganese composite hydroxide particles, method for producing same, positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing positive electrode active material for nonaqueous electrolyte secondary
WO2012131881A1